Network analysis of acute stress reaction in a sample of Chinese male military college students - Gong, Yue; Guo, Zhihua; Lu, Hongliang; Wang, Xinlu; Zhang, Yajuan; Ren, Lei; Zhu, Xia (Frontiers in Psychiatry, 2023)
Acute stress reaction (ASR) following a stressful event is associated with stress-related mental disorders. However, no studies have investigated the relationships between ASR symptom clusters. The present study aimed to provide a fine-grained understanding of the complex relationships among symptom clusters and identify the central symptom clusters of ASR using network analysis. The Acute Stress Reaction Scale (ASRS) was used to investigate the network structure of ASR in 1792 Chinese male military college students who were about to participate in an important physical fitness test. We calculated the weights of the edges connecting different symptom clusters and the central indices of 25 symptom clusters in the final network. There were five strongest edges with significantly higher weights than most other edge weights, including the edges between "Less communication" and "Isolated from others". The symptom clusters of "Somatic symptoms", "Hypoprosexia", and "Anxiety" were found to be the central nodes with the highest expected influences (primary centrality index). In conclusion, the present study explored the network structure of ASR, revealed complex connections between symptom clusters, and identified central clusters. These findings have important clinical implications, and it is suggested that the three central symptom clusters may be potential targets for effective interventions for ASR.